2011
DOI: 10.1074/jbc.m111.271155
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Raft Endocytosis and Exosomal Transport Facilitate Extracellular Trafficking of Annexin A2

Abstract: Annexin A2 (AnxA2), a Ca 2؉ -dependent phospholipid-binding protein, is known to associate with the plasma membrane and the endosomal system. Within the plasma membrane, AnxA2 associates in a Ca 2؉ dependent manner with cholesterolrich lipid raft microdomains. Here, we show that the association of AnxA2 with the lipid rafts is influenced not only by intracellular levels of Ca 2؉ but also by N-terminal phosphorylation at tyrosine 23. Binding of AnxA2 to the lipid rafts is followed by the transport along the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
150
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(163 citation statements)
references
References 63 publications
(30 reference statements)
7
150
0
1
Order By: Relevance
“…Rebinding of exteriorized ENO-1 to the cell surface closes the cycle of ENO-1 extracellular transport. A similar mechanism has been proposed to explain extracellular localization of annexin A2 (51). Nonetheless, it still remains to be elucidated which part of ENO-1 stays on the cell surface and which one is packed into exosomes and where the decision about ENO-1 sorting is made.…”
Section: Discussionmentioning
confidence: 99%
“…Rebinding of exteriorized ENO-1 to the cell surface closes the cycle of ENO-1 extracellular transport. A similar mechanism has been proposed to explain extracellular localization of annexin A2 (51). Nonetheless, it still remains to be elucidated which part of ENO-1 stays on the cell surface and which one is packed into exosomes and where the decision about ENO-1 sorting is made.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies showed that annexin A2 was an important component of exosomes in dendritic cells 40 and could be transferred from one cell to another in exosomes in a raft-associated manner. 19,41 More research is required to better understand the secretory annexins.…”
Section: Discussionmentioning
confidence: 99%
“…For example, many phosphorylated proteins appear in exosomes, including the calcium-dependent phospholipid-binding protein Annexin A2, which is enriched in cholesterol-rich lipid raft micro-domains of exosome membranes [101,108,109]. The localization of this protein depends on the phosphorylation of Tyr23, which prevents its endosomal degradation and allows its incorporation into exosomal membranes [109].…”
Section: Other Ptms In Evsmentioning
confidence: 99%
“…For example, many phosphorylated proteins appear in exosomes, including the calcium-dependent phospholipid-binding protein Annexin A2, which is enriched in cholesterol-rich lipid raft micro-domains of exosome membranes [101,108,109]. The localization of this protein depends on the phosphorylation of Tyr23, which prevents its endosomal degradation and allows its incorporation into exosomal membranes [109]. Other phosphorylated proteins found in exosomes include Tau, type 1 insulin receptor substrate (IRS-1), Crystalline alphaB (CryAB), Epidermal Growth Factor Receptor (EGFR), Na + -Cl − co-transporter (NCC), Aquaporin 2, FasL and proteins implicated in cellular processes such as apoptosis, survival and metabolism [79,101,108,[110][111][112][113][114][115][116][117] (Table 2 and Fig.…”
Section: Other Ptms In Evsmentioning
confidence: 99%